ANALISIS HAMBATAN PENERAPAN KURIKULUM 2013 PADA PEMBELAJARAN EKONOMI DI SMA SWASTA SE KOTA PEKANBARU - Wiliyanti, Wiliyanti; Gimin, Gimin; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purposes of this research are to find out the implementation of curriculum 2013 learning, the obstacles faced by teachers in implementing the curriculum 2013 learning, and the factors causing obstacles in the implementation of curriculum 2013 learning on economic learning in private high schools throughout Pekanbaru City. The design of this research is descriptive research with mixing method. The population in this study are 33 economics teachers from 18 Private High Schools in Pekanbaru who implement the Curriculum 2013. The sample of this study are 20 economic teachers from 10 Private High Schools. Data were collected by interview and questionnaire techniques. Implementation of the curriculum 2013 learning on economic learning in Private High School as Pekanbaru City included in the good category. There are nine obstacles, that is (1) lack of time, (2) the condition of the student, (3) the teacher is not used to learning with the complete elements in the preliminary and closing activities, (4) the discrepancy of the model and the learning method with the student's characteristic, 5) the implementation is not in accordance with the planning, (6) preparing the equipment to carry out the learning model, (7) the limited facilities, (8) the limitations of books, and (9) lack of teacher understanding of the curriculum 2013. The causes of the obstacles are due to the lack of teachers' ability to make good learning plans, the lack of teacher pedagogic competencies, the lack of teacher skills in closing learning, and managing the class, the students are not ready to follow the lesson, the teachers are accustomed to other activities, due to cost and time constraints to prepare equipment, facilities that available in schools are limited, lack of teacher skills in variations of instructional media, teachers less use of other learning resources other than textbooks, and still lack of training for new teachers.Key Words: Implementation, Curriculum 2013, Obstacles